Spinal Cord Ependymomas With MYCN Amplification Show Aggressive Clinical Behavior. Issue 9 (4th July 2019) - Swanson, Amy A; Raghunathan, Aditya; Jenkins, Robert B; Messing-Jünger, Martina; Pietsch, Torsten; Clarke, Michelle J; Kaufmann, Timothy J; Giannini, Caterina
Abstract: Adult spinal cord ependymomas are typically low grade and have a relatively favorable clinical course following gross total resection. We report 4 cases of anaplastic spinal cord ependymoma with MYCN amplification, an exceptionally rare finding. All cases occurred in the spinal cord of adolescent and young adult women and had morphological and immunohistochemical features of anaplastic ependymomas (World Health Organization grade III). Chromosomal microarray analysis demonstrated amplification of 2p24 (including MYCN ) in all cases. One patient died 6 months after surgery. Another patient recently had removal of metastatic nodules in the thoracic region, following gross total resection and adjuvant radiation therapy of a lumbar ependymoma 1 year previously. One patient responded well after chemotherapy but died after multiple relapses 82 months after diagnosis. We found MYCN amplification reported in 2 other ependymomas, both anaplastic and arising in the spinal cord of adult females (Brain Pathol 2001;11:133–43). One patient had multiple recurrences in the spinal cord and an intracranial metastasis. Although MYCN amplification is rare in ependymomas, the current and previously reported cases suggest that this is associated with higher-grade histology, spinal location, and often unfavorable prognosis. The clinical significance and therapeutic implications of MYCN amplification in ependymomas require further evaluation.